Knowledge organisations in less innovative regions: What factors explain the emergence and development of their links with firms? A case study in Argentina - Pasciaroni, Carolina (2018)
This paper explores the factors that condition the links between knowledge organisations and firms in a medium-sized city in Argentina. The study is motivated by two aspects related to innovation: 1) the conceptualisation of innovation as a local and urban phenomenon; 2) the growing importance of scientific knowledge generated in universities and science and technology (S&T) centres. This topic acquires special interest in Latin America based on the low innovative dynamism of firms, the high concentration of national R&D expenditure in public knowledge organisations and the weak link between such organisations and firms. Unlike other case studies, this paper adopts the theoretical approach of the regional innovation systems and employs a temporal perspective analysis. Among the main findings, the following factors condition the links at local level: 1) the influence of the national institutional context, in particular the active role of the national state; 2) the catalytic action of certain local agents; 3) the weak demand for knowledge. Based on the identification of these factors, it is expected that this paper may contribute to the formulation of policies that foster the links between knowledge organisation and firms in less innovative regions.